Influencing Factors of Green Credit Efficiency in Chinese Commercial Banks - Deng, Xiang; Hao, Haitao; Chang, Mei; Ren, Xiaohang; Wang, Lan (Frontiers in Environmental Science, 2022)
This paper is applied the Tobit panel model to analyze the driving factors of green credit efficiency by using Chinese commercial banks’ data from 2009 to 2019. Based on the undesirable-SBM-DEA model, this paper is attempted to construct the green credit evaluation index by incorporating carbon emissions, and evaluating the green credit efficiency of Chinese commercial banks. The result shows that the green credit efficiency of Chinese commercial banks is low currently. Moreover, there is a mutually significant relationship between the efficiency and profitability of commercial banks’ green credit funds. Our findings suggest that the commercial banks should pursue the scale of green credit capital and improve the efficiency of green credits to help China achieve carbon neutrality goals.